2018
DOI: 10.1111/1462-2920.14468
|View full text |Cite
|
Sign up to set email alerts
|

Importance of flagella in acute and chronic Pseudomonas aeruginosa infections

Abstract: Summary Pseudomonas aeruginosa is an environmental microorganism and a causative agent of diverse acute and chronic, biofilm‐associated infections. Advancing research‐based knowledge on its adaptation to conditions within the human host is bound to reveal novel strategies and targets for therapeutic intervention. Here, we investigated the traits that P. aeruginosa PA14 as well as a virulence attenuated ΔlasR mutant need to survive in selected murine infection models. Experimentally, the genetic programs that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 73 publications
0
13
0
Order By: Relevance
“…On the other hand, using Tn-seq with a transposon mutant library of strain PA14 in an acute pneumonia mice model, Lorenz et al . (2019) found that the flagellum and T4P were not required to cause infections [ 130 ]. In fact, mutants with transposon insertions in the pili and flagellar biogenesis operons ( pil, flg and fli operons) were enriched (positively selected) in this infection model.…”
Section: Cell Appendages and Adhesinsmentioning
confidence: 99%
“…On the other hand, using Tn-seq with a transposon mutant library of strain PA14 in an acute pneumonia mice model, Lorenz et al . (2019) found that the flagellum and T4P were not required to cause infections [ 130 ]. In fact, mutants with transposon insertions in the pili and flagellar biogenesis operons ( pil, flg and fli operons) were enriched (positively selected) in this infection model.…”
Section: Cell Appendages and Adhesinsmentioning
confidence: 99%
“…These toxins can disrupt the actin cytoskeleton of intestinal epithelial cells through glucosylation of the Rho family of GTPases to induce mucosal inflammation and the symptoms associated with CDI (Peniche et al, 2013). Other important virulence traits that impact host infection and colonization include: (i) cell wall proteins (CWPs) (Biazzo et al, 2013); (ii) tissue degradative proteases (Seddon et al, 1990;Seddon and Borriello, 1992;Borriello, 1995); (iii) flagella and fimbriae (Edwards et al, 2000;Stevenson et al, 2015;Lorenz et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Lon degrades FlhD in P. mirabilis (Rogers et al, 2016) and SwrA (a master activator of swarming motility) in B. subtilis (Mukherjee et al, 2015). In the ΔlasR transposon mutant library, lon mutants are negatively enriched during acute lung infection but not in biofilm-associated infection (Lorenz et al, 2019). In P. aeruginosa, Lon also degrades HigA, which regulates mvfR that encodes the master regulator for biofilm and motility (Guo et al, 2019).…”
Section: Discussionmentioning
confidence: 99%